Effects of Electron Affinity and Steric Hindrance of the Trifluoromethyl Group on the π‐Bridge in Designing Blue Thermally Activated Delayed Fluorescence Emitters. Issue 30 (8th May 2020) - Li, Huiting; Li, Jiuyan; Liu, Di; Huang, Tingting; Li, Deli
Abstract: To explore the correlation of the acceptor electron affinity and the molecular conformation to the thermally activated delayed fluorescence (TADF) feature, a series of d ‐π‐A molecules were designed and synthesized with triazine (Trz) as the acceptor (A) and carbazole (Cz) or tert ‐butylcarbazole (BuCz) as the donor (D). On the phenylene bridge between D and A, methyl or trifluoromethyl was incorporated close either to D or to A to tune the molecular conformation and the electron‐withdrawing ability of acceptor. Both the twist angles and the singlet and triplet energy difference (Δ E ST ) were observed strongly dependent on the type and position of the substituent on the π‐bridge. Only those molecules with trifluoromethyl locating close to the D side, namely TrzCz‐CF3 and TrzBuCz‐CF3, exhibit TADF feature, verifying that both sufficient electron affinity of the A unit and large dihedral angle between D and the π‐bridge are necessary to ensure the occurrence of TADF. The blue organic light‐emitting diodes fabricated with TrzCz‐CF3 and TrzBuCz‐CF3 achieved external quantum efficiencies of 9.40 % and 14.22 % with CIE coordinates of (0.19, 0.23) and (0.18, 0.29) respectively. This study provides practical design strategy for blue TADF materials particularly when planar and less crowded group is used as donor. Abstract : Sufficient acceptor strength and highly twisted conformation, by means of collective effects of electron withdrawing ability and steric hindrance of the trifluoromethyl group, were observed as both necessary to ensure the generation of blue thermally activated delayed fluorescence when carbazole is used as a donor.